ADVANCEMENTS AND APPLICATIONS IN SEMICONDUCTOR SPINTRONICS: HARNESSING ELECTRON SPIN FOR NEXT-GENERATION DEVICES - Kanaan Mohammad Musa (Operational Research in Engineering Sciences: Theory and Applications)
Today’s semiconductor devices use the charges of electrons and holes for tasks like light emission and signal processing. Semiconductor spintronics, a newer field, aims to exploit the spin of charge carriers to advance technologies like magnetic lasers, sensors, and transistors. Spintronics could enable the creation of memory, sensing, and logic devices with capabilities that charge-based devices can't match. This work explores the progress made with spintronic materials and devices, their current uses, and what the future might hold. A key feature of emerging spintronic logic devices is their ability to generate highly spin-polarized currents in two- and three-terminal tunnel junctions, which can lead to devices that consume much less power than traditional charge-based ones. Recent advancements in material engineering give hope for the rapid development and deployment of these new spintronic technologies.